Aquaculture Nutrition Research at the Commonwealth Scientific and Industrial Research Organisation: Maintaining Productivity and Competitiveness in Challenging Times - Rombenso, Artur; Truong, Ha; Simon, Cedric (Avances en Nutrición Acuicola, 2022)
The Australian aquaculture industry has faced new challenges brought about by the global pandemic and the consequences of which are only beginning to be fully recognised. In regards to the R&D sector, shifts in strategies for undertaking research are becoming apparent. In light of these new challenges, we aim to share our recent research and insights on maintaining productivity and competitiveness within the shrimp and fish nutrition research context.